Motion Development Program for Parents of Child with Cerebral Palsy - Rizqi Fajar Pradipta; Sri Joeda Andajani (Department of Special Education, 2017)
Development program is an effective program implemented continuously. Seeing the condition of the time children are more at home than when the child’s cerebral palsy is in school or therapy institute. So the role of parents of children cerebral palsy is very important to support the effectiveness of a mobile development program. The development goals are; 1) Describe prototype of motion building program for parents of cerebral palsy children, 2) Analyze the feasibility of developing prototype program of motion building for parents of children of cerebral palsy. This research uses R & D with 4D research design but in this research only in stage 3D or define, design, and develop because writer do not reach the stage of sale or dissemination of product considering the time limitations. The results of research that has been done, it can be seen that the development of this mobile development program has been successfully tested in assisting the process of continuous development program. This is demonstrated when a limited trial of the results of the development can help improve the effectiveness of a mobile development program that has sustainable properties to achieve the program’s objectives. The conclusion of the research are: 1) The product produced in this research is the development of motion building program for parents of children of cerebral palsy which is packed in book form, 2) This research produces decent product in the form of development of motion program for parents of cerbral palsy children. It is said to be eligible for fulfilling the criteria (a) valid according to the two validators of the material or content, (b) valid by the product design expert’s validator, (c) Category both in the researcher’s observation of the parent in understanding the movement program and applying it to the child’s cerebral palsy.Program bina gerak adalah program yang efektif dilaksanakan secara berkelanjutan. Melihat kondisi waktu anak yang lebih banyak berada dirumah dibandingkan dengan saat anak cerebral palsy berada di sekolah atau lembaga terapi. Maka peran orang tua anak cerebral palsy sangat penting guna menunjang kefektifan sebuah program bina gerak. Tujuan pengembangan adalah ; 1)Mendeskripsikan prototype program bina gerak untuk orang tua anak cerebal palsy, 2)Menganalisis kelayakan pengembangan prototype program bina gerak untuk orang tua anak cerebal palsy. Penelitian ini menggunakan R & D dengan desain penelitian 4D namun pada penelitian ini hanya pada tahap 3D atau define, design, dan develop dikarenakan penulis tidak sampai pada tahap penjualan atau penyebaran produk mengingat keterbatasan waktu. Hasil penelitian yang telah dilakukan, terlihat bahwa pengembangan program bina gerak ini telah berhasil diuji dalam membantu proses program bina gerak yang berkelanjutan. Hal ini ditunjukan pada saat Uji coba terbatas hasil dari pengembangan tersebut dapat membantu meningkatkan kefektifan dari sebuah program bina gerak yang memiliki sifat berkelanjutan untuk mencapai tujuan program tersebut. Kesimpulan penelitian adalah :1)Produk yang dihasilkan dalam penelitian ini adalah pengembangan program bina gerak untuk orang tua anak cerebral palsy yang dikemas dalam bentuk buku, 2)Penelitian ini menghasilkan produk yang layak berupa pengembangan program bina gerak untuk orang tua anak cerbral palsy. Dikatakan layak karena telah memenuh kriteria (a) valid menurut dua validator ahli materi atau isi, (b) valid menurut validator ahli desain produk, (c) Kategori baik dalam pengamatan peneliti terhadap orang tua dalam memahami program bina gerak dan menerapkannya pada anak cerebral palsy.